Association between the Absolute Baseline Lymphocyte Count and Response to Neoadjuvant Platinum-based Chemotherapy in Muscle-invasive Bladder Cancer. Issue 12 (December 2016) - Leibowitz-Amit, R.; Israel, A.; Gal, M.; Atenafu, E.A.; Symon, Z.; Portnoy, O.; Laufer, M.; Dotan, Z.; Ramon, J.; Avni, D.; Fridman, E.; Berger, R.
Abstract: Aims: Platinum-based neoadjuvant chemotherapy (NAC) improves overall survival in muscle-invasive bladder cancer (MIBC). A pathological complete response (pCR) at radical cystectomy after NAC is associated with better overall survival, but there are no established predictive biomarkers of response to NAC in MIBC. The aim of this study was to find laboratory variables associated with pCR following NAC. Materials and methods: We carried out a retrospective review of MIBC patients treated with NAC followed by radical cystectomy at the Sheba Medical Center between 2005 and 2015. Overall survival was calculated using the Kaplan–Meier product-limit method and compared between patients who achieved or did not achieve pCR using the Log-rank test. Baseline and pre-surgery laboratory values were collected and compared between patients who subsequently achieved pCR and those who did not using logistic regression. Results: Fifty-eight patients underwent radical cystectomy after NAC, with a median follow-up of 32 (range 4.8–111.4) months from diagnosis. Of 55 patients with documented pathological outcome on radical cystectomy, 17 (31%) achieved pCR (complete responders). Of the 15 complete responders with follow-up data, 13 (87%) were still alive at time of last follow-up for this study (July 2015). Patients who did not achieve pCR had a significantly worse overall survival than complete responders ( P = 0.0007). The baseline lymphocyte count, neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR) were significantly associated with response ( P = 0.037, P = 0.045, P = 0.042, respectively) on univariate analysis, whereas baseline albumin, haemoglobin, neutrophils, platelets and the total white blood count were not significantly associated with response. Lymphocyte counts were significantly higher in responders than non-responders throughout three time points ( P = 0.003 using a generalised linear mixed model). Conclusions: A high baseline level of lymphocytes is associated with the achievement of pCR at radical cystectomy after NAC, which, in turn, is associated with a significantly longer overall survival. Our results suggest that chemosensitivity in MIBC is associated with lymphocyte count. Highlights: There are no biomarkers of response to neoadjuvant chemotherapy in muscle invasive bladder cancer. Achievement of pathological complete response (pCR) at radical cystectomy is associated with improved survival. A higher pre-chemotherapy lymphocyte count was associated with pCR. Responders had higher lymphocyte counts than non-responders throughout treatment and recovery. Our results suggest that the adaptive immune arm may affect chemosensitivity.